Bioethanol production using the sodium hydroxide pretreated sweet sorghum bagasse without washing. (1st July 2016) - Yu, Menghui; Li, Jihong; Chang, Sandra; Zhang, Lei; Mao, Yueying; Cui, Ting; Yan, Zhipei; Luo, Chunliang; Li, Shizhong
Abstract: Sweet sorghum, with its multi-platform of resources of starch, sugar and cellulose, is considered a very promising energy crop to produce bioethanol. In this study, bioethanol production of sodium hydroxide (NaOH) pretreated sweet sorghum bagasse without solid substrate washing was investigated. The results showed that direct enzymatic saccharification and ethanol fermentation of NaOH pretreated solid substrate without washing significantly improved the fermentable sugars conversion and ethanol theoretical yield from 44.06 ± 0.93% and 44.85 ± 1.15% to 65.14 ± 0.19% and 61.81 ± 1.28%, respectively. Experiments where NaOH pretreated liquor (SL) was added into the thoroughly washed NaOH pretreated solid substrate showed the fermentable sugars conversion yield improved significantly. Furthermore, analysis of enzymes activities during enzymatic saccharification showed that SL maintained cellulase activity significantly, especially for that of xylanase activity. These results suggested that the NaOH pretreated lignocellulosic solid can be employed for direct enzymatic saccharification and subsequent ethanol fermentation without washing. This process would improve the sustainability and economic viability of bioethanol production.